Manajemen Sumber Daya Manusia Dalam Meningkatkan Efektifitas Pembelajaran Sains Melalui Organisasi Jurusan Di Madrasah Aliyah Nurul JadiD - A'yun, Qurrotul; Fahmadiah, Putri; Azizah, Nur (UMSU, 2024)
The Head of the Madrasah has the responsibility of implementing education, managing administration, and developing other educational personnel. They are also responsible for improving the productivity of the madrasah's human resources. This study aims to examine the organizational learning system of departments at Madrasah Aliyah Nurul Jadid in order to enhance learning effectiveness. The research method used is qualitative and follows a case study approach. Data was collected through participant observation, in-depth interviews, and documentation. The findings of this study indicate that there are three stages of development: human resource development, organizational system development, and the effectiveness of learning within the organization.